Tegmen Tympani Defect and Brain Herniation Secondary to Mastoid Surgery: Case Presentation - Oguz Kadir Egilmez; Fatih Mehmet Hanege; M. Tayyar Kalcioglu; Tuncay Kaner; Numan Kokten (Case Reports in Otolaryngology)
Brain herniation into the middle ear is very rarely seen. In addition to reasons like congenital factors, trauma, and infection, tegmen defect may develop as a result of iatrogenic events secondary to chronic otitis media surgery with or without cholesteatoma. Since it may cause life-threatening complications, patients must be evaluated and monitored for tegmen defect. In this paper, diagnosis and treatment of a brain herniation case due to iatrogenic tegmen defect were described along with relevant literature.